FRI0558 One approach to evaluating step therapy policies for immune disorder specialty pharmaceuticals. (23rd January 2014) - Ingham, M. P.; Paris, A.; Ellis, L.; Kozma, C.
Abstract : Background: Rheumatology practices are increasingly exposed to patient health care benefit plans that include designs such as "step therapy" (ST) policies which may affect medication choice. Managed care companies implement ST policies for specialty pharmaceuticals to reduce utilization of infused biologics in new patients, based on an assumption of presumed cost savings. Objectives: To assess whether managed care policies that limit access to infusion biologics (IV) in order to shift new patients to injection biologics (SQ) have had the desired effect. Methods: This analysis compared share of utilization for biologic products for plans identified with ST policies versus all other claims (Other) in a large US administrative database. Data from plans with a ST policy throughout 2010 were compared to all other biologic claims during the same time period using data from Symphony Health Solutions Corp.'s ProMetis database. This database provides a unique opportunity for this type of analysis, as they span multiple identifiable plans which can be cross-referenced to known ST policies. Available data included payer, prescription (Rx), diagnosis (Dx) and procedure (Px) claims with unique anonymised patient identifiers. For 2010, biologic claims were evaluated based on: patients with Rx data having at least one biologic prescription and patients with Rx and Px data, for the subset with ≥ 1 Rx claim (any type) and ≥ 1 medical claim (all cause). The number and percentage of patients with (or claims for) a biologic in 2010, was described. A secondary analysis using only subcutaneous (SC) products in the Rx database was conducted. Results: Sixteen different plans had a ST policy in 2010. There were 280, 271 patients (5, 960 ST and 275, 927 Other) with at least one biologic in the Rx claims, 274, 495 with at least one claim in the Rx and Px combined data (7, 936 ST and 266, 559 Other), and 271, 635 with claims for SQ biologics in the Rx data (5, 853 ST and 267, 379 Other). There was less than a 4.6% difference in patient proportions accessing any individual product, when comparing those products within ST policies vs Other. These results were consistent for all Rx, Rx and Px, and for the Rx only cohort, including when restricted to the more homogeneous data from SQ patient claims only. Hypothetically assuming an annual cost of SQ treatment of $20, 000 with a difference between SQ and IV biologics of $5000 per patient, for every 100 patients treated on each type of biologic prior to the policy change, a shift of 5 (4.6%) patients from IV to SQ after the policy change, would mean spending an additional $100, 000 on SQ to save $125, 000 on IV. This projected $25, 000 savings would be 1.0% of the original annual cost of IV. Conclusions: Policies designed to reduce overall patient proportions using infusion biologics suggest only a very modest effect in this population-level comparison. The cost benefit of implementing this type of policy for this modest effect, as well as the resource implications on practicing rheumatologists, needs to be considered. Disclosure of Interest: M. P. Ingham Employee of: Janssen Scientific Affairs, LLC, A. Paris Consultant for: Janssen Scientific Affairs, LLC, L. Ellis Employee of: Janssen Scientific Affairs, LLC, C. Kozma Consultant for: Janssen Scientific Affairs, LLC